Selection of workout test sets to monitor training gains and determine performance capacity
Tests can be repeated periodically to indicate if the work of training is improving the capacities. 1. 40 min swim for distance indicates the lowest level of stimulation necessary for aerobic adaptation to occur (EN-1 - anaerobic threshold). 2. A 20 min swim for distance indicates the level for maximum endurance stimulation (EN-2 - VO2max). 3. A 4 min swim for distance indicates the level for race-specific speed development (AN-1 lactate peak). 4. A 1 min swim for distance indicates the level for power development (AN-2 anaerobic power). 5. A test for 200 m prediction is as follows: 5 x 100 m on a 1:4 work:recovery ratio. When the 100 m times are averaged and multiplied by 2 a predication for a 200 m time is obtained. 6. A test for 400 m prediction is as follows: 5 x 200 m on a 1:1 work:recovery ratio. When the 200 m times are averaged and multiplied by 2 a prediction for a 400 m time is obtained. The determination of the distance a swimmer travels in a particular time period is easy to make in a swimming flume but difficult in a long-course pool. I suggest that swimmers be timed for distance because that is easier and more accurate for coaches and swimmers. The swimming tests cited above should be altered as follows: 1. a 4,000 m swim for time should be substituted for the 40 min swim; 2. a 2,000 m for time for the 20 min swim; 3. a 400 m for time for the 4 min swim; and 4. a 100 m for time for the 1 min swim.